A review of job tenure under the Job in Jeopardy programme in first episode psychosis. (May 2016) - Williams, Philip Lee; Lloyd, Chris
Introduction: This paper explores what happens to young people with psychosis who have competitive employment when they first engage in treatment. Method: 11 of 39 (28%) of programme participants of an individual placement and support programme who received vocational assistance under the Job in Jeopardy funding were identified. A prospective observational design was used to evaluate programme outcomes over a minimum of 6 months. Results: It is of interest that the majority of young people who were at risk of losing their job and were receiving assistance did not manage to sustain employment. At the completion of data collection only two people continued to be engaged in competitive employment. Conclusion: Although the sample is very small, there appears to be a clear trend demonstrating that being engaged in competitive employment at the point of experiencing a first episode of psychosis does not protect an individual against losing that job. It is evident that staff involved with this group of clients need to assist those with employment to maintain it. There is the potential for occupational therapists to play a key role in assisting these young people to secure and maintain meaningful occupation.